Lecanemab (BAN2401): an anti–beta-amyloid monoclonal antibody for the treatment of Alzheimer disease. (1st February 2023) - Vitek, Grace E.; Decourt, Boris; Sabbagh, Marwan N.
ABSTRACT: Introduction: Nearly a dozen monoclonal antibodies (mAbs) directed against beta-amyloid (Aβ) have been developed for the treatment of Alzheimer disease (AD), and most of these mAbs are undergoing clinical trials. Newer mAbs have targeted more specific Aβ types. Lecanemab Eisai has a high affinity for large and soluble Aβ protofibrils. Data from phase 2 clinical trials have suggested the possibility of a robust efficacy signal and manageable risk of amyloid-related imaging abnormalities (ARIAs). Lecanemab is currently being studied in phase 3 trials. Areas covered: This article briefly reviews mAbs that target Aβ in AD and discusses the biology, mechanism of action, and targets of lecanemab. Expert opinion: mAbs that target Aβ are an important focus of therapeutic development for AD, with several soon to be considered for US Food and Drug Administration approval. The experience of aducanumab informs the development of other mAbs, such as lecanemab. One consideration is the conformation of Aβ targets. Targeting monomeric species has not resulted in robust clinical efficacy, whereas targeting Aβ in the form of oligomers, protofibrils, and plaques has shown evidence of slowing clinical decline. Another consideration is that mAbs will require safety monitoring for ARIAs.